Threat Conceptions in Global Security Discourse: Analyzing the Speech Records of the United Nations Security Council, 1990–2019. - Sakamoto, Takuto (International Studies Quarterly, 2023)
Since the end of the Cold War, the notion of global security, and presumed threats to it, has undergone considerable expansion and diversification. This process has been led by the United Nations Security Council (UNSC), where active deliberations concerning "threat(s) to the peace" have taken place among major international actors. Despite a sizable accumulation of scholarly arguments, however, the defining features of the structure and dynamics of the post-Cold War security discourse remain ambiguous. To address these ambiguities, this study investigates the entire body of Council deliberations over the past three decades. Based on an original dataset consisting of policy statements delivered at the UNSC, the study employs quantitative text analysis tools, including word embedding, to examine how council members have conceived the notion of security threat in terms of the various issues and entities discussed. It shows the security discourse at the UNSC to be highly stratified and reveals the persistent and pervasive influence of terrorism and the proliferation of weapons of mass destruction, which constitute the limited common grounds shared by the Council's permanent members. These findings caution against the unconstrained use of certain theoretical constructs widely employed in other works, most notably, "securitization" and "interpretative community."